STUDI KOMPARATIF PELAKU TINDAK PIDANA NARKOTIKA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DAN HUKUM ISLAM - Wahyu Akbar Prantoko; Rachmat Ihya (JOURNAL OF LAW AND NATION, 2024)
This research examines how drug criminal sanctions are implemented against violators in accordance with Law no. 35 of 2009 concerning Narcotics and how to apply sanctions according to Islamic law. Research from the library includes this research. Research findings show that the application of penalties in Law no. 35 of 2009 concerning Narcotics towards perpetrators of drug crimes relating to Articles 116, 121, 133 and 134. The findings of this research also show that the punishment of ta'zir, as stipulated in Islamic law, can be imposed on those who commit drug- related offences. According to the judge's policy, there are several types of punishment for ta'zir, including beatings, detention, publication, punishment in the form of property, and others. He believes that this form of punishment can have a deterrent effect on both the perpetrator and other people. Both the use of illegal substances and drug laws are prohibited. Similar to the prohibition of drinking alcoholic beverages according to certain hadiths and the holy Koran, narcotics and the consumption of illegal drugs are also prohibited. Apart from that, some academics think there are sanctions.